New effective sorbents for purification of aqueous media from technogenic contaminants - Blank, T.A.; Belikov, K.N.; Bryleva, K.Yu.; Shcherbakov, I. B.-Kh.; Chebanov, V.A.; Muravyova, E.A.; Saraev, V.E.; Zviagin, I.M.; Komykhov, S.A.; Ostras, K.S.; Chernenko, V.N. (Functional Materials, 2017)
Created are the sorbents based on silica gel non-covalently modified with partially hydrogenated heterocyclic compounds (PHHC), containing nitrogen as donor atoms for purification of aqueous media from technogenic contaminants. The investigations show that the modified silica gel is characterized by a sorption capacity relatively higher than that of unmodified one. The sorption degree of metal ions is studied depending on their concentrations, total mineralization and pH value of the solutions. Conditions for selective sorption of microquantities of Eu³⁺ which has been used as chemically identical to ²⁴¹Am are described. Moreover it was shown that PHHC modified silica gel was potential to use as the sorbent to concentrate the Eu³⁺ and Sr²⁺ metal ions with initial concentrations near 1 mg∙L⁻¹ for the quantitative analysis. Also the possible mechanism of metal ion sorption on the developed sorbents was proposed. Remove selected